The influence of the mode of administration in the dissemination of three coliphages in chickens - Oliveira, A. (2009)
Escherichia coli can cause severe respiratory and systemic infections in chickens, and it is often associated with significant economic losses in the poultry industry. Bacteriophages (phages) have been shown to be potential alternatives to the antibiotics in the treatment of bacterial infections. To accomplish that, phage particles must be able to reach and remain active in the infected organs. The present work aims at evaluating the effect of the route of administration and the dosage in the dissemination of 3 coliphages in the chicken’s organs. In vivo trials were conducted by infecting chickens orally, spray, and i.m. with 106, 107, and 108 plaque-forming units/mL suspensions of 3 lytic phages: phi F78E (Myoviridae), phi F258E (Siphoviridae), and phi F61E (Myoviridae). Birds were killed 3, 10, and 24 h after challenge and the phage titer was measured in lungs and air sacs membranes, liver, duodenum, and spleen. When administered by spray, the 3 phages reached the respiratory tract within 3 h. Oral administration also allowed all phages to be recovered in lungs, but only phi F78E was recovered from the duodenum, the liver, and the spleen. These differences can be explained by the possible replication of phi F78E in commensal E. coli strains present in the chicken gut, thus leading to a higher concentration of this phage in the intestines that resulted in systemic circulation of phage with consequent phage in organs. When phages were administered i.m., they were found in all of the collected organs. Despite this better response, i.m. administration is a nonpracticable way of protecting a large number of birds in a poultry unit. In general, the results suggest that oral administration and spray allowed phages to reach and to remain active in the respiratory tract and can, therefore, be considered promising administration routes to treat respiratory E. coli infections in the poultry industry.